2016
DOI: 10.1021/acs.iecr.6b01284
|View full text |Cite
|
Sign up to set email alerts
|

SrCoxFe1–xO3−δ Oxygen Sorbent Usable for High-Temperature Pressure-Swing Adsorption Process Operating at Approximately 300 °C

Abstract: Oxygen sorption/desorption properties of SrCo x Fe1–x O3−δ were examined as an oxygen sorbent for a high-temperature pressure-swing adsorption (HT-PSA) process. Perovskite-type structure of the SrCo x Fe1–x O3−δ powder samples was observed in the composition range of 0 ≤ x ≤ 0.85, by using XRD measurements. A temperature-programmed-desorption (TPD) measurement revealed that the oxygen desorption temperature in N2 for the perovskite-type SrCo x Fe1–x O3−δ samples was lowered with increasing x. Consequently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…Recently, SrFeO 3 based oxygen sorbents have received many research interests, owing to its large oxygen capacity and low operating temperature [40][41][42]. The versatile structure of SrFeO 3 offers many opportunities to introduce dopants at A and/or B site to further tuning the redox property [43][44][45]. By co-doping of Ca and Co at A and B sites respectively, oxygen partial pressure swing can be operated between 0.05 and 0.2 atm to achieve 1 wt% oxygen capacity at 400 • C-500 • C based on our recent study [46].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SrFeO 3 based oxygen sorbents have received many research interests, owing to its large oxygen capacity and low operating temperature [40][41][42]. The versatile structure of SrFeO 3 offers many opportunities to introduce dopants at A and/or B site to further tuning the redox property [43][44][45]. By co-doping of Ca and Co at A and B sites respectively, oxygen partial pressure swing can be operated between 0.05 and 0.2 atm to achieve 1 wt% oxygen capacity at 400 • C-500 • C based on our recent study [46].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, perovskite-type materials have been studied intensively in the past years for a wide range of applications, including thermochemical water splitting, SOFC and high temperature pressure swing adsorption (HT-PSA). [27][28][29][30][31] The basic crystal structure of perovskites is cubic (Pm% 3m), although deviations in their composition (e.g. by cation substitution) can generate distortions of the ideal cubic lattice structure.…”
mentioning
confidence: 99%
“…27 When the complete reduction of the perovskite ABO 3 occurs, it transforms to its defect-ordered variant brownmillerite (ABO 2.5 ), with an orthorhombic basic crystal structure (Ibm2). 27 29,32 For example, Mishra et al 33 performed DFT studies on the effect of dopants such as Sr and Fe in CaMnO 3 and found that the dopants enhance the O 2 donation properties of the material through a distortion of the lattice structure and changes in the oxygen coordination.…”
mentioning
confidence: 99%
See 2 more Smart Citations